If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3r + -11 = 25 Reorder the terms: -11 + 3r = 25 Solving -11 + 3r = 25 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 3r = 25 + 11 Combine like terms: -11 + 11 = 0 0 + 3r = 25 + 11 3r = 25 + 11 Combine like terms: 25 + 11 = 36 3r = 36 Divide each side by '3'. r = 12 Simplifying r = 12
| 7k+21=0 | | 20=5y+25 | | log(2)(3x-7)=3 | | 3x^4-3x^3+2x^2-x+10=0 | | y+5=-(x-4) | | 1x-3x=36 | | 16+5x-2=4-5x | | -6(7x-3)=144 | | 1-2x+x=9 | | y-3=-(x+4) | | X-5x=48 | | 2745+3453= | | -5(-3x+6)=120 | | 7(x-2)=3(x+2)+5(x-6) | | .4w+2.45=8.75 | | 25/7 | | n^(3/2)=125 | | 7/25 | | 29j+2=27j+6 | | 4(-8+7x)=-312 | | 3(9-4a)-19=32 | | 3/16t^8-3/12t^7 | | p-q=rs+tfor*r | | -24=-6f | | (9*10^6)1/2 | | 3(x+3)+6=5x-2(-5+x) | | y-5=-8(x+2) | | y+40=-8x+2 | | y+5=-8(x-2) | | b-6a=-3for*b | | -4x+24-4x^2=0 | | y+40=-8(x+2) |